Phosphorus remobilization from rice flag leaves during grain filling: an RNA‐seq study. Issue 1 (27th June 2016) - Jeong, Kwanho; Baten, Abdul; Waters, Daniel L. E.; Pantoja, Omar; Julia, Cecile C.; Wissuwa, Matthias; Heuer, Sigrid; Kretzschmar, Tobias; Rose, Terry J.
Summary: The physiology and molecular regulation of phosphorus (P) remobilization from vegetative tissues to grains during grain filling is poorly understood, despite the pivotal role it plays in the global P cycle. To test the hypothesis that a subset of genes involved in the P starvation response are involved in remobilization of P from flag leaves to developing grains, we conducted an RNA‐seq analysis of rice flag leaves during the preremobilization phase (6 DAA) and when the leaves were acting as a P source (15 DAA). Several genes that respond to phosphate starvation, including three purple acid phosphatases ( OsPAP3, OsPAP9b and OsPAP10a ), were significantly up‐regulated at 15 DAA, consistent with a role in remobilization of P from flag leaves during grain filling. A number of genes that have not been implicated in the phosphate starvation response, OsPAP26, SPX‐MFS1 (a putative P transporter) and SPX‐MFS2, also showed expression profiles consistent with involvement in P remobilization from senescing flag leaves. Metabolic pathway analysis using the KEGG system suggested plastid membrane lipid synthesis is a critical process during the P remobilization phase. In particular, the up‐regulation of OsPLDz2 and OsSQD2 at 15 DAA suggested phospholipids were being degraded and replaced by other lipids to enable continued cellular function while liberating P for export to developing grains. Three genes associated with RNA degradation that have not previously been implicated in the P starvation response also showed expression profiles consistent with a role in P mobilization from senescing flag leaves.